Long-lived pancreatic ductal adenocarcinoma slice cultures enable precise study of the immune microenvironment. (3rd July 2017) - Jiang, Xiuyun; Seo, Y. David; Chang, Jae Hyuck; Coveler, Andrew; Nigjeh, Eslam N.; Pan, Sheng; Jalikis, Florencia; Yeung, Raymond S.; Crispe, Ian N.; Pillarisetty, Venu G.
ABSTRACT: Pancreatic ductal adenocarcinoma (PDA) remains a deadly disease that is rarely cured, despite many recent successes with immunotherapy for other malignancies. As the human disease is heavily infiltrated by effector T cells, we postulated that accurately modeling the PDA immune microenvironment would allow us to study mechanisms of immunosuppression that could be overcome for therapeutic benefit. Using viable precision-cut slices from fresh PDA, we developed an organotypic culture system for this purpose. We confirmed that cultured slices maintain their baseline morphology, surface area, and microenvironment after at least 6 d in culture, and demonstrated slice survival by MTT assay and by immunohistochemistry staining with Ki-67 and cleaved-Caspase-3 antibodies. Immune cells, including T cells (CD3 +, CD8 +, and FOXP3 + ) and macrophages (CD68 +, CD163 + and HLA-DR + ), as well as stromal myofibroblasts (αSMA + ) were present throughout the culture period. Global profiling of the PDA proteome before and after 6 d slice culture indicated that the majority of the immunological proteins identified remain stable during the culture process. Cytotoxic effects of drug treatment (staurosporine, STS and cycloheximide, CHX) on PDA slices culture confirmed that this system can be used to assess functional response and cell survival following drug treatment in both a treatment time- and dose-dependent manner. Using multicolor immunofluorescence, we stained live slices for both cancer cells (EpCAM + ) and immune cells (CD11b + and CD8 + ). Finally, we confirmed that autologous CFSE-labeled splenocytes readily migrate into co-cultured tumor slices. Thus, our present study demonstrates the potential to use tumor slice cultures to study the immune microenvironment of PDA.